Monitoring State Compliance with the UN Convention on the Rights of the Child : An Analysis of Attributes - Vaghri, Ziba; Zermatten, Jean; Lansdown, Gerison; Ruggiero, Roberta; Vaghri, Ziba; Zermatten, Jean; Lansdown, Gerison; Ruggiero, Roberta (Springer Nature, 2022)
This open access book presents a discussion on human rights-based attributes for each article pertinent to the substantive rights of children, as defined in the United Nations Convention on the Rights of the Child (UNCRC). It provides the reader with a unique and clear overview of the scope and core content of the articles, together with an analysis of the latest jurisprudence of the UN Committee on the Rights of the Child. For each article of the UNCRC, the authors explore the nature and scope of corresponding State obligations, and identify the main features that need to be taken into consideration when assessing a State$1 (Bs progressive implementation of the UNCRC. This analysis considers which aspects of a given right are most important to track, in order to monitor States' implementation of any given right, and whether there is any resultant change in the lives of children. This approach transforms the narrative of legal international standards concerning a given right into a set of characteristics that ensure no aspect of said right is overlooked. The book develops a clear and comprehensive understanding of the UNCRC that can be used as an introduction to the rights and principles it contains, and to identify directions for future policy and strategy development in compliance with the UNCRC. As such, it offers an invaluable reference guide for researchers and students in the field of childhood and children$1 (Bs rights studies, as well as a wide range of professionals and organisations concerned with the subject.s
English
Keywords: Education; Human rights; Public administration; Political economy; Open Access; Children$1 (Bs rightss; Children's well-being; Civil and political rights; State$1 (Bs compliances; Social policy; Protection measures from exploitation; UN Committee on the Rights of the Child; Government accountability; Rights monitoring; Community Well-Being